Elsevier's integrated immunology and microbiology - Actor, Jeffrey K. (Mosby/Elsevier, 2007)
The book presents immune system components, both innate and adaptive, in the concise manner to elucidate their interwined relationships that culminate in effective host protection and health. It also presents the world of microbiology, with a concise overview of clinically relevant bacteria, viruses, fungi, and parasites, to allow an understanding of infectious organisms as the causative agents underlying human disease